Johann Wolfgang von Goethe As a 'Representative Man' in Interpretation by the American Philosopher Ralph Waldo Emerson - G.V. Alekseeva (Ученые записки Казанского университета: Серия Гуманитарные науки, 2018)
The article is based on the material of L.N. Tolstoy’s personal library at Yasnaya Polyana and discusses his reading interest in the essay by Ralph Waldo Emerson, an American poet and transcendentalist philosopher, included into his book “Representative Men”, a copy of which has been preserved in the writer’s book collection. An assumption has been made that R.W. Emerson’s essay “Goethe; or, the Writer” published in the above-mentioned book was familiar to L.N. Tolstoy as early as the 1850s. As decades passed, R.W. Emerson remained for long among L.N. Tolstoy’s favorite readings. From this fact, a number of extracts from R.W. Emerson’s article about J.W. v. Goethe have been considered in their actual or possible dialogue with certain ideas of the Russian writer. R.W. Emerson’s opinion on J.W. v. Goethe’s works expressed through such notions as “duty”, “writer’s vocation” coincides with L.N. Tolstoy’s view set out in the essay entitled “What Is Art?” (“Chto takoe iskusstvo?”). Quite in the spirit of L.N. Tolstoy sounds R.W. Emerson’s idea that J.W. v. Goethe “cannot be precious to humanity” as he was not capable of obeying “the unlimited power of moral duty”. R.W. Emerson was confident that a raw talent alone is not enough for writing: behind any work should be an individual having his own principled view on the world and society. The mentioned similarities make the image of J.W. v. Goethe in R.W. Emerson’s perception dichotomous: on the one hand, he is a standard, a role model of the writer, while, on the other hand, J.W. v. Goethe was incapable of obeying the sense of morality, which prevented him from realization of the uniqueness of human personality.